Simulation toolbox for in-situ combustion applied to experimental setups (2016)
Abstract: A simulation Toolbox, exclusively designed for the analysis of different experimental setups for in-situ combustion (ISC) analysis, was developed. This Toolbox can be targeted for the analysis of chemical kinetics. The models in the Toolbox are based on fundamental conservation laws, physical correlations for porous media properties and property databases available in the open literature. The Toolbox, written in Matlab, is coupled to CANTERA, a software for the analysis of complex chemical mechanisms and thermodynamics for gas phase reactions. The toolbox considers three main applications: kinetic cell, plug flow reactor and combustion tube. Each one can be applied to the analysis of different issues in ISC experiments, as illustrated throughout the thesis. The kinetic cell module, as its name indicates, is particularly suitable for the analysis of these experimental setups. It includes the ability to follow gas phase reactions. This module is used with the GRI-Mech 3.0, a complex reaction mechanism originally designed to model natural gas combustion, that includes 325 reactions and 53 species to address the existence of CO oxidation in the gas phase of ISC experiments. The plug flow reactor module, modeled as a series of kinetic cells, simplifies computation and is suitable for the design of experiments that reduce the existence of concentration gradients in a kinetic cell. The last module can model a combustion tube including Darcy's flow and fundamentals of flow in porous media. It captures important phenomena such as oil plugging as it includes pressure balance, based on volume conservation principles and thermodynamic relations. The analysis with these three modules represents an ideal complement to reservoir modeling software that, while suitable for the study of oil production in field has not been designed for the complex processes that take place in in-situ combustion experiments